Formulation and development of some BCS Class II drugs - Marapur, SC; Jat, Rakesh Kumar; Patil, J S (Journal of Drug Delivery and Therapeutics, 2019)
The aim of this research was to develop and evaluate liquisolid compacts of Ezetimibe a bcs class II drug. The series of formulations containing Ezetimibe drug were formulated by using aerosil a colloidal silicone dioxide and avicel PH microcrystalline cellulose in different ratios by using suitable solvent. Solubility studies were performed in propylene glycol and polyethylene glycol (PEG-200, 400, 600) for the choice of the best non volatile liquid to dissolve Ezetimibe. On the basis of the solubility data PG was chosen as a good solvent for the Ezetimibe. Ezetimibe was dissolved in solvent PG for the preparation of solution of drug. The coating and carrier materials transferred to the drug solution and added 5% of disintegrating agent (Croscarmellose) was mixed completely and the blend is compressed into compacts. Formulated compacts were evaluated for all post compression parameters and the in-vitro drug release study was carried out. All the formulations have shown a very good drug release in 15 min except compressibility problems due to higher812 loading factor of liquid vehicle for the formulations. The selected formulation F11 containing 30% of drug solution has shown good drug release of 100.01% in 15 min compared to dissolution of pure drug and marketed tablet which shown 45.5% and 81.6 % respectively.No interactions were found between drug and polymers in FITR as well as DSC. XRD of selected formulation shows that drug present in the formulation is in amorphous form. Keywords: Ezetimibe HCl, Avicel PH, Aerosil 200, Propylene glycol, liquisolid compacts